A Ubiquitous Publish/Subscribe Platform for Wireless Sensor Networks with Mobile Mules - Tong, Xiaoyu; Ngai, Edith C.H. (2012 IEEE 8th International Conference on Distributed Computing in Sensor Systems, 2012)
Existing publish/subscribe architectures for wirelesssensors networks only support stationary sensors interconnectedwith each other. They cannot handle mobile sensors or remotesensors that are sparsely deployed. In this paper, we propose anovel ubiquitous publish/subscribe system that supports data accessfrom both mobile sensors and stationary sensors. Our systemutilizes mobile phones as data mules to relay subscriptions andpublished data between broker and remote sensors. It providescontent-based publish/subscribe services from sensors deployedanywhere without depending on any network infrastructure. Weimplement our publish/subscribe platform on real hardwaresand test it in a hiking trail application. The application allowsusers to subscribe for sensing data from both stationary sensorsand mobile sensors along hiking trails. Extensive experimentsare conducted in an outdoor testbed to evaluate the systemperformances such data delay, number of data received andcommunication overhead.